If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(y-1)-(y-2)=6(y+3)
We move all terms to the left:
8(y-1)-(y-2)-(6(y+3))=0
We multiply parentheses
8y-(y-2)-(6(y+3))-8=0
We get rid of parentheses
8y-y-(6(y+3))+2-8=0
We calculate terms in parentheses: -(6(y+3)), so:We add all the numbers together, and all the variables
6(y+3)
We multiply parentheses
6y+18
Back to the equation:
-(6y+18)
7y-(6y+18)-6=0
We get rid of parentheses
7y-6y-18-6=0
We add all the numbers together, and all the variables
y-24=0
We move all terms containing y to the left, all other terms to the right
y=24
| 8x-3x+2x=1 | | 8+x=106 | | 8-x=106 | | x-66=1016 | | 2.5j+1.5=0 | | -(-7+i)=5.5 | | 66+x=1016 | | -12(1/2)+h=-8.5 | | 3z+8=2020 | | 8x-1=3x-3 | | 5e+4=-65 | | 8(d-0)=32 | | -2c+-5=29 | | 4x^+20=120 | | 9p+4p=12-7 | | -3x=504(x+1) | | x-x*0.4=17.4 | | 7s-94=65 | | r+67=912 | | 64=t+22 | | -0.1x^2+2.4x+8.1=10 | | 83=p+9 | | v-16=34 | | -5w+3(w-3)=5 | | c+59=61 | | t+32=39 | | m+5=78 | | 5(6x+10)=2(15x+25) | | 6(m-5)=(m+29) | | 5(6x+10)=30x-x | | h-3=42 | | 5(6x+10)=2(15x+10) |